The Outcome Of Laparoscopic Pyloromyotomy Using Electrocautery Hook For Treatment Of Infantile Hypertrophic Pyloric Stenosis (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background:   Laparoscopic pyloromyotomy first described in 1991, has become an effective minimally invasive treatment for IHPS. Recently, in most of the paediatric surgery centers laparoscopic pyloromyotomy has become popular. We can use multiple techniques to perform laparoscopic pyloromyotomy such as-hook electrocautery, retractable pyloromyotomy knife, arthrotomy knife, ophthalmic knife, bovie blade. Among them in our study we have tried to evaluate the outcome of  laparoscopic pyloromyotomy using electrocautery hook.Objective: To evaluate the outcome of laparoscopic pyloromyotomy using electrocautery hook for treatment of infantile hypertrophic pyloric stenosis (IHPS).Materials and Methods: This is a prospective type of observational study was conducted in the department of Paediatric surgery, Dhaka Medical College & Hospital, from September 2024 to December 2025. The study included infants of 2 weeks to 12 weeks of age, Documented pyloric stenosis proven by abdominal USG (Pyloric Canal length ≥ 15mm, Pyloric muscle thickness ≥ 3mm) & excluded  infants with previous abdominal surgery. Inflamed or unhealed umbilicus, associated with known case of congenital heart disease/severe congenital anomaly, redo cases. In this study, 24 patients was done by laparoscopic pyloromyotomy using electrocautery hook. Laparoscopic pyloromyotomy was done under general endotracheal anesthesia. Per operative events and postoperative outcome were followed up after 1 weeks and 1 months. Data were analyses using descriptive statistics.Results: In this study maximum number of patients 11(45.8%) were between 2- 5 weeks of age. Mean ± SD of age was 4.47 ± 2.01 weeks. Out of 24 cases, male and female were 19(79.1%) and 5(20.8%) respectively. Male: Female ratio was 3.8: 1.Ultrasound findings revealed that pyloric muscle thickness was 5.42±1.03 mm and pyloric canal length was 18.9±2.74 mm. Diameter of pylorus was 17.5± 1.56 mm. The mean operative time was 43.5±6.1 min with a range of 30-70 min. No bleeding, but 1(4.1%) case found mucosal perforation. Only 1 (4.16%) case developed postoperative complication like omental herniation. In this study complete recovery was found 23(95.8%) of patients.Conclusion: This study revealed that laparoscopic pyloromyotomy using electrocautery hook is safe, technically feasible and effective with good postoperative outcomes.Journal of Paediatric Surgeons of Bangladesh (2024) Vol. 15 (1 & 2): 33-38